The Effect Cow Manures and Cocopeat on the Growth of Falcataria mollucana in Used Oil Contaminated Soil Media - Basuki Wasis; Anistya Safa Fitriani (Jurnal Silvikultur Tropika, 2022)
Used oil waste contains the accumulation of metals in soil which causes a decrease in soil quality and could be pollutant that can poison the soil with the result that can affect the environment. Sengon (Falcataria mollucana) seedlings, cow manure and cocopeat are materials used to improve soil that has been contaminated with used oil. This study aims to analyze the effect of cow manure and cocopeat on the growth of the seedlings with an optimal dosage. The results showed that the application of cow manure and cocopeat increased the growth of seedlings and improved soil fertility that was contaminated with used oil. The application of cow manure had a significant effect on height, diameter, total wet weight, total dry weight, and root length. The S2C4 treatment (60 g of cow manure + 100 g of cocopeat) gave optimal results on diameter and total dry weight, S3C4 (90 g cow manure + 100 g cocopeat) on root length, S2C0 (60 g of cow manure) for shoot root ratio, S3C0 treatment (90 g of cow manure) for total wet weight, S1C2 (cow manure 30 g and cocopeat 50 g) for seed height. Keywords: cocopeat, cow manure, Falcataria mollucana, used oil waste